2020
DOI: 10.1002/jor.24776
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative serum biomarker of circulating collagen X effectively correlates with endochondral fracture healing

Abstract: Currently, there are no standardized methods for quantitatively measuring fracture repair. Physicians rely on subjective physical examinations and qualitative evaluation of radiographs to detect mineralized tissue. Since most fractures heal indirectly through a cartilage intermediate, these tools are limited in their diagnostic utility of early repair. Prior to converting to the bone, cartilage undergoes hypertrophic maturation, characterized by the deposition of a provisional collagen X matrix. The objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…26 markers, often reported in fracture repair studies, include tartrateresistant acid phosphatase (TRAP), receptor activator of nuclear factor kappa beta ligand (RANKL), and c-terminal telopeptide (CTX) reflecting osteoclast activity, alkaline phosphatase, procollagen type 1 N-terminal polypeptide, and osteocalcin reflecting osteoblast activity, CXM and collagen X reflecting chondrocyte activity and transforming growth factor beta, tumor necrosis factor-a (TNF-a), and vascular endothelial growth factor reflecting immune activity and angiogenesis. [29][30][31][32] Assessment of these biomarkers may elucidate how underlying fracture repair processes are altered in various circumstances, manifesting in distinct repair outcomes. [29][30][31][32] Furthermore, recent reviews have investigated the potential of these biomarkers to serve as independent predictors of fracture repair success.…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…26 markers, often reported in fracture repair studies, include tartrateresistant acid phosphatase (TRAP), receptor activator of nuclear factor kappa beta ligand (RANKL), and c-terminal telopeptide (CTX) reflecting osteoclast activity, alkaline phosphatase, procollagen type 1 N-terminal polypeptide, and osteocalcin reflecting osteoblast activity, CXM and collagen X reflecting chondrocyte activity and transforming growth factor beta, tumor necrosis factor-a (TNF-a), and vascular endothelial growth factor reflecting immune activity and angiogenesis. [29][30][31][32] Assessment of these biomarkers may elucidate how underlying fracture repair processes are altered in various circumstances, manifesting in distinct repair outcomes. [29][30][31][32] Furthermore, recent reviews have investigated the potential of these biomarkers to serve as independent predictors of fracture repair success.…”
Section: Biomarkersmentioning
confidence: 99%
“…[29][30][31][32] Assessment of these biomarkers may elucidate how underlying fracture repair processes are altered in various circumstances, manifesting in distinct repair outcomes. [29][30][31][32] Furthermore, recent reviews have investigated the potential of these biomarkers to serve as independent predictors of fracture repair success. [33][34][35] This is of particular interest as reliable correlations could enable earlier clinical identification of nonunion, improving clinical outcomes.…”
Section: Biomarkersmentioning
confidence: 99%
“…[21][22][23] Collagen X (ColX) is the hallmark of hypertrophic cartilage and is specifically expressed as cartilage converts to bone during development and endochondral fracture healing. 24 A number of studies indicated that PTH has potential for cartilage repair through promoting the proliferation of hypertrophic chondrocytes 25 and inhibiting chondrocyte hypertrophy. [26][27][28] The changes in the expression levels of Sox9, Col2a1, MMP-13, and ColX during the cartilage healing process after mandibular condylar fractures and whether the application of PTH can regulate Sox9 expression and promote condylar cartilage healing need to be studied in more depth.…”
Section: Impact Statementmentioning
confidence: 99%
“…Some authors report more rapid bone regeneration in male rats and mice compared to females ( Mehta et al, 2011 ; Deng et al, 2020 ). However, there are also studies showing no sex-specific differences in murine fracture healing ( Collier et al, 2020 ; Working et al, 2020 ). In many studies, data generated from female and male mice are pooled together, simply stipulating that there would be no sex-specific difference in the healing process.…”
Section: Introductionmentioning
confidence: 99%